Estratégias como práticas sóciodiscursivas em uma universidade pública: uma abordagem crítica - Baêta, Odemir Vieira (2016)
This thesis deals with the applicability of the sociological approach of strategy as social and discursive practice in a Federal University of Viçosa. The aim was to understand the process of formation of strategies showing the insertion of the institution in the macro-social context. The socio-historical reconstruction of the university was presented highlighting particular political, social, cultural and administrative. The process of formation of strategies have been evidenced through strategy as social and discursive practice. The unveiling of the legitimation process considering their ideological and political aspects were presented. The theoretical discussions that supported the thesis is based in the Strategy as Practice. The Critical Realism was the philosophical assumption that based throughout the conduct of research methodological field understanding organizational phenomenon of strategy. The theoretical and methodological framework of Critical Discourse Analysis offered support for the analysis of discursive practices. Instruments for implementation of data collection was to define the documentary research performed in public archives of the university. As the generation of data were used the non-participant observation and in-depth interview unstructured photo-elucidation. They selected 42 historical and contemporary photographs that served as a guide for interactions during interviews significantly aiding in generating data for the formation of the narratives that were presented in the analysis of social practices and discursive practices. The field research was conducted on the spot on the campus of the Federal University of Viçosa with 48 interviews. The main strategies as identified and represented by the subjects practices were internationalization, protection and welfare, extension and social communication. Although the analyzes and the results demonstrate the presence of strong hegemonic and ideological components that contribute to the efficiency and effectiveness of processes of research, education and extension at the university, the study also identified reflective subjects who question the model with focus on productivity and competitiveness gift the institution as a result of a modern society and a capitalist system in force. actions that identify social subjects as protagonists in key strategic practices as set out in the Strategy as Practice approach that advocates the effective participation of the subject in the formation of strategies through their daily activities in the workplace were observed.